2017
DOI: 10.2196/mental.6713
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Optional Videoconferencing-Based Treatment of Alcohol Use Disorders: Randomized Controlled Trial

Abstract: BackgroundTreatment of alcohol use disorders (AUDs) is characterized by an adherence rate below 50%. Clinical research has found that patient adherence enhances treatment effect; hence, health authorities, clinicians, and researchers strive to explore initiatives contributing to patients receiving treatment. Concurrently, videoconferencing-based treatment is gaining ground within other addiction and psychiatric areas.ObjectiveThe aim of this study was to test whether optional videoconferencing increases adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 38 publications
(58 reference statements)
1
56
0
3
Order By: Relevance
“…Four studies focused on individual video counseling for smoking cessation [ 31 , 70 - 72 ], 3 studies focused on alcohol consumption [ 73 - 75 ], 3 studies focused on physical activity [ 76 - 78 ], and 3 studies focused on obesity [ 79 - 81 ]. No trial examined the effectiveness of real-time video counseling on nutrition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies focused on individual video counseling for smoking cessation [ 31 , 70 - 72 ], 3 studies focused on alcohol consumption [ 73 - 75 ], 3 studies focused on physical activity [ 76 - 78 ], and 3 studies focused on obesity [ 79 - 81 ]. No trial examined the effectiveness of real-time video counseling on nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…No trial examined the effectiveness of real-time video counseling on nutrition. Most trials were funded by grants from the government [ 76 , 77 , 79 - 81 ] or university [ 71 , 73 ]. One study reported receiving no funding [ 75 ], 1 study was funded by the Craig H. Neilsen Foundation [ 78 ], and 1 study was funded by CureApp Inc [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in Europe, where there is no tradition for giving participants in studies a financial reward ( Weinstock, Capizzi, Weber, Pescatello, & Petry, 2014 ). Many trials recruit fewer patients than anticipated ( Brown et al, 2009 ; Brown et al, 2014 ; Nielsen & Nielsen, 2018a ; Tarp, Bojesen, Mejldal, & Nielsen, 2017 ). Thus, to be able to consider to which extent findings may be generalized, it is crucial to know how the participating patients in the study differ from non-participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical applications of social VR have thus far been scarce. There are a number of possible uses of social VR in CBT: social VR could be used as an immersive type of videoconferencing psychotherapy (Tarp et al 2017), virtual gatherings could be used as a form of behavioral activation in depression (Lindner et al 2019a), a patient in non-automated VR exposure therapy would likely benefit from observing an embodied avatar therapist modeling non-phobic responses (Olsson and Phelps 2007;Öst 1989), VR could also make it convenient to perform VR exposure therapy for public speaking anxiety (Kahlon et al 2019) in front of avatars instead of agents, and more.…”
Section: Social Vrmentioning
confidence: 99%